THE MEANING OF TECHNICAL AND ALLOCATIVE EFFICIENCY IN EDUCATION FINANCING IN SECONDARY SCHOOLS IN THE ERA OF DECENTRALIZATION - Anis Widayati; Rujianto; Imanuel Yosua Lonteng; Ramika Dilla; Widyatmike Gede Mulawarman; Nurhadi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Effective management of education funding is crucial to ensuring the quality and sustainability of education, particularly in secondary schools, which often face significant financial challenges. This study aims to understand the meaning of technical and allocative efficiency in education funding in secondary schools in the era of decentralization. Using a qualitative approach, the study explores the experiences, perceptions, and strategies of school stakeholders including principals, teachers, and financial managers in managing educational resources. Data .were collected through in-depth interviews, observations, and document analysis, then analyzed thematically to uncover emerging patterns and meanings. The results indicate that technical efficiency is understood as a school's ability to maximize the use of funds to support effective teaching and learning, while allocative efficiency is defined as the alignment of budget distribution with educational priority needs and the local context. The era of decentralization provides space for schools to be more independent in decision making, but also poses challenges in maintaining a balance between resource constraints and demands for quality improvement. These findings emphasize the importance of managerial capacity and transparency in education funding and provide implications for policies that promote accountability and equitable access to education at the regional level.